Inovasi Teknologi Kristalisasi Serbuk Instan Kombinasi Jahe dan Kencur guna Meningkatkan Pengetahuan dan Ketrampilan di Desa Wirun - Adiningsih, Retnowati; Setiawan, Iwan; BAKRI, DZAKI FIKRI FIRDAUS (Lembaga Dongan Dosen, 2023)
Cardiovasculer diseases are the main causes of death in the world with 32% of total deaths. Hypertension is one of the main risk factors for cardiovascular disease, so it needs special attention in society. Ginger (Zingiber officinale Rosc) and galangal (Kaempferia galanga) are medicinal plants and easy to found at home, so it can the best solutions for long term treatment of hypertension. Community service activities were carried out for the Kelompok Wanita Tani (KWT) in Wirun, Mojolaban, Sukoharjo. This research includes analysis of public knowledge regarding hypertension, education on the benefits of product as antihypertensives, education on making crystal powder from ginger and galangal and final evaluation. The results of the research show that this community service activity can produce crystal powder products from ginger and galangal that are easy, cheap and can help lower blood pressure in the people of Wirun Village. This crystal powder products from traditional plants can be a business opportunity for KWT from Wirun as a Produksi Industri Rumah Tangga (PIRT).